Pengaruh Kombinasi Buah Jeruk Nipis dan Buah Mengkudu Terhadap Mortalitas Pediculus humanus capitis - Sayekti, Fitria Diniah Janah; Qurrohman, Muhammad Taufiq; Priyandari, Damar Ajeng; Srikandini, Chris (At-Taqaddum, 2020)
Head lice (Pediculus humanus capitis) greatly interferes with human activity because it can cause itching of the head, redness and severe infections. The use of natural insecticides is recommended, because natural insecticides are considered safer. Potential anti lice plants are lime and noni. The combination of the two is believed to have a more effective effect on head lice mortality. This study aims to study and determine the effect of a combination of lime juice and noni on the mortality of Pediculus humanus capitis. The concentration of lime and noni which are used are 25%, 50%, 75% and 100%, respectively. The combination of test materials used was 25% limes 75% noni; 50% lime 50% noni; 75% lime and 25% noni, negative control and positive control. The combination of the extract of noni and lime juice had the highest mortality effect on Pediculus humanus capitis with a concentration of 25% combination of lime; 75% noni.